A megújuló energiaforrások, főként a szélenergia felhasználása a világban, Európában, Ukrajnában és Kárpátalján - Hadnagy István; Гаднадь Іштван; Hadnagy Istvan (My University, 2022)
A tanulmány a megújuló energiaforrások, azon belül főként a szélenergia hasznosításának helyzetével foglalkozik a világban, Európában és Ukrajnában az üzembe helyezett megújuló energiaforrást felhasználó berendezések összteljesítménye alapján. Nemzetközi összehasonlításban bemutatásra kerül a szélenergia ipar fejlődése, jelenkori helyzete és lehetőségei Ukrajnában, valamint Kárpátalján. A szerző saját kutatási eredményei alapján jellemzi a szélenergia-fejlesztés lehetőségeit Kárpátalján.

Abstract. The study deals with the state of the use of renewable energy sources, especially wind energy, in the world, in Europe and in Ukraine, based on the total capacity of the installed devices using renewable energy sources. In an international comparison will be presented the development, current state and opportunities of the wind energy industry in Ukraine and Transcarpathia. Based on her own research results, the author characterizes the possibilities of wind energy development in Transcarpathia.
The use of renewable energy sources, especially wind energy, in the world, in Europe, in Ukraine and in Transcarpathia
Keywords: megújuló energiaforrások; szélenergia; szélerőmű; Ukrajna; Kárpátalja